2022
DOI: 10.53819/81018102t2099
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style and Financial Performance of Commercial Banks in Kenya

Abstract: This study aimed at establishing the influence of leadership style on the financial performance of commercial banks operating in Kenya. The study adopted a positivist philosophy, correlational and cross-sectional research deigns and a target population comprising management staff working in commercial banks. 385 respondents were selected from 10,395 management staff. Primary data was collected using structured questionnaires with data being analyzed using both descriptive and inferential statistics. Parametric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…These results were supported by regression analysis indicating that democratic and transformational leadership explained 17.4% and 22.1% of variance in ROA and ROE respectively. In contrast, autocratic leadership demonstrated a positive but statistically insignificant effect on the same parameters, indicating that while potentially useful in certain scenarios, it may not be universally beneficial (Mwangi et al, 2022). These findings align with Puni et al (2014) who found no significant relationship between any leadership style (transformational, transactional, or laissez-faire) and financial performance in Ghanaian banks, although democratic leadership had a slightly stronger correlation.…”
Section: Literature Reviewsupporting
confidence: 57%
See 1 more Smart Citation
“…These results were supported by regression analysis indicating that democratic and transformational leadership explained 17.4% and 22.1% of variance in ROA and ROE respectively. In contrast, autocratic leadership demonstrated a positive but statistically insignificant effect on the same parameters, indicating that while potentially useful in certain scenarios, it may not be universally beneficial (Mwangi et al, 2022). These findings align with Puni et al (2014) who found no significant relationship between any leadership style (transformational, transactional, or laissez-faire) and financial performance in Ghanaian banks, although democratic leadership had a slightly stronger correlation.…”
Section: Literature Reviewsupporting
confidence: 57%
“…Several studies have found that democratic and transformational leadership styles positively impact financial performance in commercial banks. For example, a study on leadership style and financial performance in commercial banks in Kenya showed that democratic and transformational leadership had a significant positive influence on return on assets (ROA) and return on equity (ROE) (Mwangi et al, 2022). These results were supported by regression analysis indicating that democratic and transformational leadership explained 17.4% and 22.1% of variance in ROA and ROE respectively.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Good CG goes beyond conventional ethical standards and encourages top managers and senior executives to regulate their behavior with a focus on greater responsibility and leadership roles within businesses. CG ensures that company directors and administrators prioritize efficient and equitable protection for all shareholders (Mwangi, 2022). In recent years, the Kenyan banking sector and the broader region have experienced several bank collapses and increased merger and acquisition activities due to weak CG frameworks.…”
Section: Problem Statementmentioning
confidence: 99%